'I Considerably Miscalculated, Though Everyone Else Did, Too': Colonel-General Erich Hoepner's Private Letters On The Road To Leningrad (May–September 1941). Issue 3 (3rd July 2021) - Stahel, David
ABSTRACT: The German invasion of the Soviet Union in 1941 is typically reconstructed from military files that offer a dispassionate view, recording events rather than opinions. Gaining insights into the minds of key German commanders is much more difficult and often a matter of speculation, which all too often reflects the supposition of the author rather than anything concrete about the protagonist. Yet almost every German general wrote letters home to their wives and families in which — from the available examples — they offered surprisingly frank commentaries on the conduct of their operations. One such insightful collection is by Colonel-General Erich Hoepner, the commander of Panzer Group 4 in Operation Barbarossa in 1941.